SYSTEMATIC LITERATURE REVIEW THE ROLE OF AUTHENTIC LEADERSHIP AND ORGANIZATIONAL COMMITMENT IN IMPROVING EMPLOYEE WORK PEFORMANCE IN THE ERA OF DIGITAL TRANSFORMATION - Adinda Kinaryosih; Amanda Pradita Nurul Febrianti; Muh.Khoeri; Dani Rizana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research examines the role of organizational commitment and authentic leadership in improving employee productivity in the face of digital transformation. Using a systematic literature review approach, this research examines the interaction between these two factors to achieve the best outcomes for employees. Authentic leadership, which emphasizes transparency, integrity and accountability, creates a supportive work environment where employees are valued and treated fairly. On the other hand, organizational commitment, which measures employees' emotional and psychological well-being towards the organization, contributes to higher levels of loyalty and performance that support organizational goals. The findings of this study suggest that the combination of organizational commitment and authentic leadership significantly improves employee productivity, especially in a rapidly changing environment. Therefore, organizations are encouraged to invest in leadership development and create an environment that encourages employees to react.